Inter-brain synchrony in real-world and virtual reality search tasks using EEG hyperscanning - Ashkan F. Hayati; Amit Barde; Ihshan Gumilar; Abdul Momin; Gun Lee; Alex Chatburn; Mark Billinghurst; Mark Billinghurst (Frontiers in Virtual Reality)
This study investigates inter-brain synchronization during a collaborative visual search task performed in Virtual Reality (VR), and compares it to the same task executed in a real-world environment. Previous research has demonstrated that collaborative visual search in real-world settings leads to measurable neural synchrony, as captured through EEG hyperscanning. However, limited work has explored whether similar neural dynamics occur in immersive VR. In this study, we recorded EEG hyperscanning data from participant pairs engaged in a joint visual search task, conducted in both VR and physical settings. Our results reveal that inter-brain synchronization occurred in the VR condition at levels comparable to the real world. Furthermore, greater neural synchrony was positively correlated with better task performance across both conditions. These findings demonstrate that VR is a viable platform for studying inter-brain dynamics in collaborative tasks, and support its use for future team-based neuroscience research in simulated environments.